Factors Associated with Iron and Folic Acid Deficiency Among Pregnant Women a Cross-Sectional Hospital-Based Study - Fakharunissa; Hingoro, Rasheeda; Ahmed, Waqarunissa (Pakistan Journal of Medical & Health Sciences, 2022)
Current study is a cross-sectional hospital-based study and its comparative results were highly significant (<0.005). When 200 pregnant women after dividing into two different groups compared with each other regarding their folic acid and iron intake during three trimesters of their pregnancies results were significant (<0.005). In the multiple regression analysis three variables iron, folic acid and hemoglobin levels were analyzed. In Group X, and Group Y the levels of iron (167.2± 3.12, 165.12±4.11, 164.33±2.13), (67.1± 4.12, 15.12±6.11, 14.33±2.13) folic acid (16.4±2.4, 16.4±1.5, 17.1±2.3), (6.4±1.4, 10.4±1.8, 5.1±1.3) and hemoglobin (15.2±3.6, 15.5±2.11, 15.5±3.12) (10.2±3.6, 7.5±32.10, 8.5±11.12) were calculated respectively. The percentage mean standard deviation of Spinal bifida, Anencephaly and Premature birth in Group X and Group Y was (1.21±1.01, 1.11±1.11, 1.22±2.2 ), (7.41±5.3, 3.17±2.14, 17.12±12.22).